Tradisi Pembacaan Sahîh} Bukhâri di PP. Mambaus Sholihin Gresik Telaah Genealogis - hasan, mochamad ismail (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2021)
this article aims to explore genealogicaly reading of Sahîh} Bukhâri tradition held in Mambaus Sholihin boarding school. According to Dhofier’s research, methods of tradisional teaching in boarding school are Sorogan, Bandongan and Musyawarah. Mambaus Sholihin boarding school led by kiai Masbuhin Faqih is islmic education institution that has maintained such three methods. However, it is in this boarding school that there has been other method too. It is reading of book collectively by all participant and the explanation of the book content is nothing at all. The book read by them is Sahîh} Bukhâri. The result of genealogicaly tracing showed that the tradition of such reading meets it’s root in one of Yemenis muslims traditions, the Middle East. This tradition was brought by them when they had immigrated to Nusantara, especially to Java. Some of them arrived and stayed in Gresik up to now. In other hand, they are believed on the line of descent of Muhammad prophet, who delivered Islam teachings. Thus, they achived Javanese Muslims’s welcome and respect, especially boarding school people’s, including kiai Masbuhin Faqih, leader of Mambaus Sholihin boarding school. One of Yemenis muslims traditions who have stayed in Gresik is annual reading of Sahîh} Bukhâri fully in Rajab. This same tradition has been adopted and practiced by kiai Masbuhin Faqih in his boading school fully in Rajab too.Keywords: Mambaus Sholihin boarding school, Sahîh} Bukhâri, Genealogic, Yemenis muslims tradition.